2015
DOI: 10.1007/s00467-015-3120-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of rituximab in a pediatric patient with therapy-resistant nephrotic syndrome

Abstract: BackgroundRituximab (RTX) has recently been introduced as a second-line therapy for nephrotic syndrome in children. Studies show that RTX given during the nephrotic state may be less effective than treatment during a non-nephrotic state, possibly due to loss of RTX in the urine.Case-Diagnosis/TreatmentWe describe a 10-year-old boy with steroid-resistant nephrotic syndrome (SRNS) treated with RTX during a phase of active non-selective proteinuria. The serum half-life of RTX in this patient was less than 1 day c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 16 publications
1
32
0
1
Order By: Relevance
“…Bundan başka, yeni yapılan bir çalışmada SDiNS'li ço-cuklarda rituksumabın idrarla kaybı ve üçüncü boşluklara (asit, plevral efüzyon) dağılımı nedeni ile yarı ömrü çok kısa bulunmuş (normalde 20 gün, SDiNS'de <1 gün) ve bu ajanın SDiNS'de başarısız-lığında bu durum bir etken olarak ileri sürülmüş-tür. 79 …”
Section: Ri̇tuksi̇mabunclassified
“…Bundan başka, yeni yapılan bir çalışmada SDiNS'li ço-cuklarda rituksumabın idrarla kaybı ve üçüncü boşluklara (asit, plevral efüzyon) dağılımı nedeni ile yarı ömrü çok kısa bulunmuş (normalde 20 gün, SDiNS'de <1 gün) ve bu ajanın SDiNS'de başarısız-lığında bu durum bir etken olarak ileri sürülmüş-tür. 79 …”
Section: Ri̇tuksi̇mabunclassified
“…In this patient, the half-life of rituximab was reported to be less than a day [1]. The use of population pharmacokinetic modeling that factored in elimination and distributive sites enabled delineation of the pharmacokinetic profile of rituximab in the patient with nephrotic syndrome [1]. Interestingly, Mo et al reported the pharmacokinetics of rituximab in autoimmune cytopenias exhibited by chronic lymphocytic leukemia (CLL) patients; where a rapid clearance of rituximab was observed in all the patients during the first cycle of treatment rendering undetectable trough concentrations of rituximab [2].…”
mentioning
confidence: 92%
“…The authors postulated the existence of other possible mechanisms that may possibly explain the rapid clearance of rituximab. In this patient, the half-life of rituximab was reported to be less than a day [1]. The use of population pharmacokinetic modeling that factored in elimination and distributive sites enabled delineation of the pharmacokinetic profile of rituximab in the patient with nephrotic syndrome [1].…”
mentioning
confidence: 98%
See 2 more Smart Citations